P3.110 Relationship Between Violence and HIV Infection Among Female Sex Workers in Benin. (13th July 2013) - Tounkara, F K; Guédou, F; Ahoussinou, C; Zannou, D M; Kpatchavi, A; Kintin, F D; Avery, L; Bédard, E; Bitera, R; Alary, M
Abstract : Objective: In Africa, there are few studies examining female sex workers (FSWs) vulnerability to physical, sexual and psychological violence and how this influences their HIV risk. This study sought to assess the types, frequency and factors associated with violence among FSWs and examined the relationship between violence and HIV prevalence. Methods: Data from an integrated biological and behavioural survey (Benin, 2012), were used to analyse the frequency of physical, sexual and psychological violence. We also created a violence score using the number of violence types experienced by FSWs. Multivariable logistic regression analysis controlling for potential socio-demographic and behavioural confounders was used to assess the association between violence and HIV. Results: Among the 1016 FSWs recruited in this survey, 17.1%, 13.3% and 33.4% reported having experienced, at least once in the past 30 days, physical, sexual and psychological violence, respectively. Condom breakage was strongly and significantly associated with all 3 types of violence (P < 0.0001). HIV prevalence was 20.39%. In the multivariable analysis, the adjusted odds ratio (AOR) for the association between HIV prevalence and physical violence was 1.59 (95% confidence interval [95% CI]: 1.01–2.51). The corresponding AORs for sexual and psychological violence were 1.67 (95% CI: 1.02–2.72) and 1.60 (95% CI: 1.10–2.33), respectively. Exposure to a larger number of violence types was associated with a progressively increasing HIV prevalence: AOR = 1.39 for one type of violence, AOR = 1.75 for two types and AOR = 2.43 for three types (p = 0.005, test for trend). Conclusions: This study shows an association between exposure to three different forms of violence and HIV prevalence among FSWs in Benin. Although violence could also be a consequence of an HIV-positive status, it is also likely to be a distal determinant of HIV acquisition. Interventions are needed to reduce violence towards FSWs; this should be integrated into HIV prevention programmes.